(untitled) (Fiep Bulletin - online, 2019)
The Crossfit® is a model of physical training that works with high intensity and involves several muscle groups during thevariety of its exercises, so, the objective of this research was to evaluate the performance of athletes of (CF) after the"Workout of the Day" (WOD) specific of the method, through the levels of lactate pre and post-training and maximum oxygenvolume (VO2max). The research consisted of seven athletes aged between 18 and 35 years, CF practitioners for at leasttwelve months, with a training frequency of at least five times a week. The research methodology was based on thecollection of anthropometric measurements, such as weight and height, and the Cooper test. The WOD was the "Filthy Fifty"and the dosage of lactate obtained in duplicate by one of the researchers, through the collection of a drop of blood from thedigital pulp of the ring finger revealing the athlete’s ability to perform a physical exercise anaerobically. Analyzing the resultsof the Cooper test, we found that men achieved excellent aerobic performance, and women superior. As for lactate there wasno significant difference compared to each other, but when compared to other sports, such as swimming for example, in theWOD, lactate concentration was higher. Due to the mentioned facts, we can conclude that the athletes accumulated a greatamount of energy produced by the anaerobic system in the training. And in relation to VO2max, it was verified that they havean excellent aerobic fitness when their results were compared with the Cooper table.